2011
DOI: 10.1029/2011jd016243
|View full text |Cite
|
Sign up to set email alerts
|

Within-canopy sesquiterpene ozonolysis in Amazonia

Abstract: [1] Through rapid reactions with ozone, which can initiate the formation of secondary organic aerosols, the emission of sesquiterpenes from vegetation in Amazonia may have significant impacts on tropospheric chemistry and climate. Little is known, however, about sesquiterpene emissions, transport, and chemistry within plant canopies owing to analytical difficulties stemming from very low ambient concentrations, high reactivities, and sampling losses. Here, we present ambient sesquiterpene concentration measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
110
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(122 citation statements)
references
References 75 publications
8
110
0
Order By: Relevance
“…For example, the in-canopy ozonolysis of sesquiterpenes (τ ≈ 1-2 min) has been estimated to consume 0.6-1.5 nmol·m −2 ·s −1 (7-28%) of the downward ozone flux and 46-61% of the sesquiterpenes mass in Amazonia (48). Approximately 6% of the ozone flux at this site is required to account for the entire formic acid flux.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the in-canopy ozonolysis of sesquiterpenes (τ ≈ 1-2 min) has been estimated to consume 0.6-1.5 nmol·m −2 ·s −1 (7-28%) of the downward ozone flux and 46-61% of the sesquiterpenes mass in Amazonia (48). Approximately 6% of the ozone flux at this site is required to account for the entire formic acid flux.…”
Section: Resultsmentioning
confidence: 99%
“…CC BY 4.0 License. sesquiterpenes concentrations can peak at ground level rather than within the canopy (Jardine et al, 2011), though the applicability of this result to the boreal forest is unclear.…”
Section: Vertical Gradient In No 3 Reactivitymentioning
confidence: 99%
“…Filella et al (2007) concluded that algorithms which use only incident irradiance and leaf temperature as drivers to predict VOC emission rates may be inadequate. As the review of Holopainen and Gershenzon (2010) has shown, the interaction of multiples stresses, both biotic and abiotic, provides a great potential to alter VOC emission. It is most likely that other environmental factors such as drought, ozone and CO 2 concentrations can amplify or attenuate such alterations in the emission responses to temperature and light .…”
Section: E Bourtsoukidis Et Al: Ozone Stress As a Driving Force Of mentioning
confidence: 99%
“…Enclosure approaches "cannot be used to estimate emission rates without the exclusion or corrections of ozone and disturbance effects during the studies" (Jardine et al, 2011). In order to correct for ozone destruction during the sampling process, selected branch emissions were studied by GC-MS technique at the Finnish Meteorological Institute in Helsinki and compared with the chemical analysis performed earlier at Mainz University (Münz, 2010) for the site of interest.…”
Section: Emission Calculationmentioning
confidence: 99%
See 1 more Smart Citation